Construção do conhecimento e ensino superior no Brasil: Um estudo sobre a articulação histórico-ontológica entre trabalho, formação humana e conhecimento e os impactos do neoliberalismo - Alcantara, Elton Luiz da Costa (2023)
The research presented here proposed to carry out a study on the impacts of neoliberalism on Brazilian higher education as a space for articulation between knowledge production and human formation. In our analysis, we seek to present the historical-ontological relationship between work, knowledge and education, its materialization in the capitalist way of living, oriented to the self-expanding logic of capital – which is reflected in the bourgeois ideological decadence and in the replacement of the historical split between theory and practice in the "school of reading" and "school of doing", the latter for the subaltern class while the former is aimed at the dominant sectors. We also address the historical development of Brazilian higher education, a country of hyper-late capitalist formation, through a colonial path, which is expressed in the way its university institution is constituted, erected through the initiatives "from above" of the State. In addition, we intend to demonstrate the transformations that have occurred in the sociometabolism in the face of the structural crisis of capital, impacting all dimensions of life, including knowledge. In this sense, we understand "postmodernism" as a fruit (and contribution) of these times. Being a deepening form of ideological decadence, it opens the way to irrationalism and the acceptance (even if by indirect apology) of pseudoscientific explanations by accepting any "truth" as equally valid, promoting the hypercentrality of subjectivity. In view of this, we work on the hypothesis that this general context has gained particularized dimensions in Brazil in the last three decades: it is expressed through a constant application, in different intensities and modalities, of neoliberal measures, impacting universities and, in them, the capacity to produce knowledge and training that are not focused on market interests. The studies confirmed this hypothetical scenario, pointing to the exponential growth of the private university sector, along with the trafficking of business models and concepts into the public sphere, forming a "operacional university". In addition, there was a constant withdrawal of funds for research and training in Brazilian public higher education from 2014/16 onwards. For the development of the research, we started from the historical-dialectical materialist theoretical-methodological framework in a bibliographic study, referring to classic and contemporary Marxist authors who elaborated on work, knowledge, education, university in Brazil and neoliberalism.